Multicomponent semiconductor structures in the construction of solar cells - Бабыченко, О.Ю. (Radiotekhnika, 2017)
The solar cells are presented as the main cells of alternative energy systems. Conditions and basic designs for the effective operation of solar cells are considered. The main requirements for the technologies for their production and mathematical models are presented.